Comforting Cow Dung into Eco-Briquettes: A Rural Energy Solution in East Java - Alqodiri, Achmad Viqi; Aisyah, Siti; Hastuti, Umi Nur; Prasetyo, Yudy; Andayani, Endah Alamsari (Jurnal Abdimas Kartika Wijayakusuma, 2025)
This community engagement project was conducted in Cendono Village, East Java, aiming to transform cow dung into charcoal briquettes as a sustainable energy solution. The main objective was to educate and empower local cattle farmers through a community-based research (CBR) approach. Activities included awareness sessions, training, and hands-on briquette production. Participants were taught the complete process, including drying, mixing, molding, and testing the briquettes. The trial phase showed that the briquettes produced optimal burning duration and sufficient heat output for household cooking. This initiative served as both a waste management strategy and an economic empowerment tool. Results demonstrated successful community adoption of the briquette-making process, improved awareness of sustainable practices, and the potential to generate supplementary income for rural families. Additionally, the initiative contributed to reducing unmanaged cow dung waste, thus preventing environmental and health issues. This program illustrates the potential of organic waste transformation into renewable energy sources. The experience is expected to inspire other rural communities to adopt similar environmentally friendly and economically beneficial practices.